2017
DOI: 10.1088/1361-6560/aa90ff
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an adaptive local thresholding method on CBCT and µCT endodontic images

Abstract: Root canal segmentation on cone beam computed tomography (CBCT) images is difficult because of the noise level, resolution limitations, beam hardening and dental morphological variations. An image processing framework, based on an adaptive local threshold method, was evaluated on CBCT images acquired on extracted teeth. A comparison with high quality segmented endodontic images on micro computed tomography (µCT) images acquired from the same teeth was carried out using a dedicated registration process. Each se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
0
22
0
9
Order By: Relevance
“…The volumes were then binarized to visualize only filling material remnants. The filling material was quantified in mm 3 after canal filling and the two stages of the secondary treatment procedure (Michetti et al 2017). The localization of the filling material remnants was determined for the coronal, middle and apical thirds.…”
Section: Micro-ct Analysismentioning
confidence: 99%
“…The volumes were then binarized to visualize only filling material remnants. The filling material was quantified in mm 3 after canal filling and the two stages of the secondary treatment procedure (Michetti et al 2017). The localization of the filling material remnants was determined for the coronal, middle and apical thirds.…”
Section: Micro-ct Analysismentioning
confidence: 99%
“…Another study, using high spatial resolution cone beam tomography (76μm) showed very strong correlations between root canal areas obtained from selected slices in CBCT and histologic sections 23 or root canal volume obtained by micro-CT data 24 . In both cases, the automatic segmentation implemented resulted in CBCT data which was slightly smaller than the gold standard (underestimation), corroborating results of the present study.…”
Section: Discussionmentioning
confidence: 96%
“…The enhanced images were also compared as 3-D volumes. The canal root was segmented from the 3-D volume using a dedicated adaptive local thresholding described in [50]. For visually showing the segmentation results, the software MeVisLab [51] was used.…”
Section: Metricsmentioning
confidence: 99%
“…The segmentation results were analyzed quantitatively as well. For each root, the canal area and the Feret's diameter were estimated for all the radicular axial reconstructions, as suggested in [50]. The Feret's diameter defines the longest distance between two parallel straight lines that are tangent to the shape.…”
Section: Metricsmentioning
confidence: 99%